Analisis Prilaku Ibu Rumah Tangga di Perkotaan Terhadap Pemanfaatan Teknologi Aquavertikulture Inovasi Pengembangan Budidaya Pertanian dan Perikanan pada Lahan Sempit - Dani, Erfan; Windiana, Livia; Ocvanny, Nur (Universitas Islam Balitar, 2018)
Urban is the destination and center of all community activities. According to Harahap,(2013) states that each population has a significant increase and population growth.Communities living in cities are highly demanded to have high productivity in order tocompete and meet their individual needs. But it cannot be denied that there are some urbancommunities who are not able to compete with the population. The profession of ahousewife in one example is a society that is not competitive and unproductive. Based onnational socio-economic survey data from the Central Bureau of Statistics (2004) statedthat most mothers in cities from 40 years who have children are 63.3% of households and29.6% of them are career women. This is because being a housewife in a city depends moreon the husband's income. Lately in Indonesia there has been considerable economicupheaval in various sectors that have enabled an increase in various needs in variousregions of Indonesia. This condition requires housewives to play the brain to supportfamily needs. Aquaverticuture insulation of agricultural development and efforts inincreasing productive business of housewives is a solution that can be offered insupporting the economy, this implementation program will be implemented in thecommunity of housewives in urban areas, while the areas to be piloted in this program arethe Circle of Friends Dahlia and Gardania at Sulfate Gardens Housing, PandanwangiVillage, Blimbing, Malang City.